Humoral Immunity vs. Salmonella - Takaya, Akiko; Yamamoto, Tomoko; Tokoyoda, Koji (Frontiers in Immunology, 2020)
In primary infection with Salmonella, it has been reported - without consideration of Salmonella’s functions - that humoral immunity plays no role in the clearance of bacteria. In fact, Salmonella targets and suppresses several aspects of humoral immunity, including B cell lymphopoiesis, B cell activation, and IgG production. In particular, the suppression of IgG-secreting plasma cell maintenance allows the persistence of Salmonella in tissues. Therefore, the critical role(s) of humoral immunity in the response to Salmonella infection should be re-investigated. The suppression of IgG plasma cell memory strongly hinders vaccine development against non-typhoidal Salmonella (NTS) because Salmonella can also reduce humoral immune memory against other bacteria and viruses, obtained from previous vaccination or infection. We propose a new vaccine against Salmonella that would not impair humoral immunity, and which could also be used as a treatment for antibody-dependent autoimmune diseases to deplete pathogenic long-lived plasma cells, by utilizing the Salmonella’s own suppression mechanism of humoral immunity.